Evaluation of the Biolog Substrate Utilization System To Identify and Assess Metabolic Variation among Strains of Xanthomonas campestris pv. Citri - Verniere, C. (1993)
Metabolic fingerprints of 148 strains of Xanthomonas campestris pv. citri originating from 24 countries and associated with various forms of citrus bacterial canker disease (CBCD) were obtained by using the Biolog substrate utilization system. Metabolic profiles were used to attempt strain identification. Only 6.8% of the studied strains were correctly identified when the commercial Microlog 2N data base was used alone. When the data base was supplemented with data from 54 strains of X. campestris pv. citri (40 CBCD-A strains, 8 CBCD-B strains, and 6 CBCD-C strains) and data from 43 strains of X. campestris associated with citrus bacterial spot disease, the percentage of correct identifications was 70%. Thus, it is recommended that users supplement the commercial data base with additional data prior to using the program for identification purposes. The utilization of Tween 40 in conjunction with other tests can help to differentiate strains associated with CBCD and citrus bacterial spot disease. These results confirmed the separation of X. campestris pv. citri into different subgroups (strains associated with Asiatic citrus canker [CBCD-A], cancrosis B [CBCD-B], and Mexican lime canker [CBCD-C]). The utilization of l-fucose, d-galactose, and alaninamide can be used as markers to differentiate strains associated with these groups. A single strain associated with bacteriosis of Mexican lime in Mexico (CBCD-D) was closely similar to CBCD-B strains.